KONSTRUKSI DAN HASIL TANGKAPAN ALAT TANGKAP JARING INSANG (GILL NET) YANG BEROPERASI DI DESA SEMERAP KABUPATEN KERINCI PROVINSI JAMBI - Dobid Idma Wijaya; Syafrialdi Syafrialdi; Mohd Yusuf Amrullah (SEMAH Jurnal Pengelolaan Sumberdaya Perairan, 2022)
Gill nets are widely used by Semerap Village fishermen to catch fish in Lake Kerinci. Various forms of construction, placement of nets, and the number of sheets of nets are thought to influence the catch on the fish's number, size, weight, length, and height. The research objectives were to identify the construction and analyze the types of fish caught in gill nets operating in Semerap Village, Kerinci District, Jambi Province. The research method used is survey and observation. The results showed that the construction of gill nets operating in Semerap Village, Kerinci Regency obtained relatively the same dimensions, with only striking differences such as mesh size, fishing area, ballast size used, operating time, and target fish. The types of fish caught were dominated by Tilapia, Hampala Sp., Anabas Sp., Trichogaster Sp., and Rasbora Sp.